2020
DOI: 10.1111/liv.14510
|View full text |Cite
|
Sign up to set email alerts
|

Influence of donor and recipient gender on liver transplantation outcomes in Europe

Abstract: Background & Aims: The impact of gender and donor/recipient gender mismatch on LT outcomes is controversial. The aim of this study was to compare outcomes of LT in Europe, using the ELTR database, between male and female recipients, including donor/recipient gender mismatch. Methods: Recipient, donor and transplant characteristics were compared between male and female patients. Patient survival was compared between groups, and the impact of donor/recipient gender matching as well as donor and recipient anthrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 27 publications
(48 reference statements)
1
31
1
1
Order By: Relevance
“…Female sex is a possible risk factor for steatosis after transplant but features of MS were found to be more frequent in males in an Italian cohort of LT recipients. 129 Furthermore, male patients presented a significantly lower survival rate when transplanted for metabolic disease compared with female patients in a European study 123 ; however, this results still need to be confirmed in other cohorts before an accurate interpretation can be drawn. Besides sex differences, a recent meta-analysis examining 17 studies, representing 2,378 post-LT patients, found the 5-year incidence rates for recurrent NAFLD to be 82% and the rate of cirrhosis from 1% to 11%.…”
Section: Long-term Post-transplant Complicationsmentioning
confidence: 95%
See 2 more Smart Citations
“…Female sex is a possible risk factor for steatosis after transplant but features of MS were found to be more frequent in males in an Italian cohort of LT recipients. 129 Furthermore, male patients presented a significantly lower survival rate when transplanted for metabolic disease compared with female patients in a European study 123 ; however, this results still need to be confirmed in other cohorts before an accurate interpretation can be drawn. Besides sex differences, a recent meta-analysis examining 17 studies, representing 2,378 post-LT patients, found the 5-year incidence rates for recurrent NAFLD to be 82% and the rate of cirrhosis from 1% to 11%.…”
Section: Long-term Post-transplant Complicationsmentioning
confidence: 95%
“…Therefore, even though women have lower MELD scores than men as a result of lower median creatinine levels with the same degree of renal impairment, the higher number of women listed, together with the fact that NASH is becoming the first indication for LT, could theoretically outweigh the disadvantage previously posed for women to LT access for other indications. Nevertheless, in a recent ELTR analysis, the overall number of LT performed in Europe constantly increased until 2007; however, the percentage of male patients significantly increased over time, whereas female recipients significantly decreased 123 . Thus, NASH women remain longer on the waiting list for transplant, are more likely to be removed, have a higher risk of death and are less likely to receive LT compared to men with NASH, even when adjusting for potential confounding covariates.…”
Section: Nash As Indication For Liver Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…This model allowed the assessment of covariate effects on the subdistribution for graft failure. Variables selected for inclusion in the multivariable models were based on previously identified factors associated with post‐LT patient and graft survival [1,20–26]. A P ‐value <0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…Newer scores have also been developed, such as the Liver Graft Assessment Following Transplantation (L‐GrAFT) [13] and Early Allograft Failure Simplified Estimation (EASE)[14] scores, which focus on early allograft dysfunction. Some workgroups have created simplified scores (such as Kong et al., who included recipient age, creatinine, bilirubin and albumin (Alb) [15]) or focused on individual parameters, such as post‐operative platelet counts [5], body mass index (BMI) [16], recipient blood type [17] or recipient and donor gender as prognostic markers [18].…”
Section: Introductionmentioning
confidence: 99%